The world a traveller's guide to the planet - Gourlay, Will (Lonely Planet, 2014)
Every country in the world, in one guidebook: Lonely Planet delivers the first guide to The World. This user-friendly A-Z gives a flavour of each country in the world, including a map, travel highlights and info on where to go and how to get around. In Lonely Planet's trademark bluespine format, this is the ultimate planning resource